EFL Students’ Duolingo English Practice Test Difficulties: A Comparative Study Between Low and High Achievers - Nurlian, Nurlian; Maulina, Maulina; Amin, Syarif (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigated the difficulties encountered by both high- and low-achieving EFL students when finishing the Duolingo English Test (DET) Free Practice Version. applying a qualitative descriptive comparative design, data information was gathered using semi structured conversations with five students. Results indicate that although the DET platform was initially perceived as accessible and supported by clear instructions, students still experienced linguistic, technical, and psychological challenges. Limited vocabulary and grammar, time pressure, spontaneous responses in speaking and writing, and unstable connections were the most frequently reported difficulties, especially among low-achievers. High-achievers appeared more confident and employed more effective strategies, enabling them to better adapt to the adaptive test format. These results suggest that achievement level influences how students cope with the demands of digital assessments. This research highlights the requirement for focused preparation and improved methods support to help EFL learners better navigate DET tasks.